Deriving structural perfection in the structure of polyacrylonitril-based electrospun carbon nanofibers. (June 2019) - Kim, Doo-Won; Kim, Chang Hyo; Yang, Cheol-Min; Ahn, Seokhoon; Kim, Yang Hui; Hong, Seung Ki; Kim, Kyung Soo; Hwang, Jun Yeon; Choi, Go Bong; Kim, Yoong Ahm; Yang, Kap Seung
Abstract: In the fabrication of carbon nanofibers via the electrospinning system, the conformation of the polymer chains of organic nanofibers play significant roles in imparting structural perfection of the carbon nanofibers. We observed morphological variation of polyacrylonitrile based electrospun carbon nanofibers by controlling take-up speed, followed by stretching process. The observed domain structure on the surface of carbon nanofiber was closely related to their microstructure as well as their physical properties, such as crystallinity and electrical conductivity.